Study of accelerated corrosion test method for 16MnR steel waste containers in backfill materials. (19th May 2019) - Lu, Y. F.; Li, S. S.; Zhao, H. Y.; Yang, J. C.; Deng, L. R.; Xu, Y.; Yang, B. B.
ABSTRACT: To research the long-term corrosion of 16MnR steel radioactive waste container in backfill materials that are lightweight aggregate concrete (LWAC) and Keerjian bentonite, accelerated corrosion test in the backfill environment was studied. The corrosive products during accelerated tests were compared to the ones during simulated tests through morphology observation, component analysis by XRD and grey correlation quantitative evaluation. An approach of the accelerated corrosion test combining enhancing medium with dry-wet alternation was designed. In either LWAC and bentonite enviroment, the corrosion rates of accelerated test and simulated test are quite different, but their corrosion products, corrosion laws and corrosion development trend are similar. For the zinc coating, the correlation coefficients of the accelerated test in LWAC and bentonite was 0.672 and 0.734, respectively. Moreover, the accelerated speedup of the designed accelerated corrosion test is greater than 337. Therefore, the designed accelerated corrosion test method has satisfactory correlation and acceleration effect.